Innovation of Arduino Uno-Based Physics Practicum Tool with MAX4466 Sound Sensor - Muhammad Khairul Annam Najahy Najahy; Supurwoko; Lita Rahmasari (Universitas Airlangga, 2023)
The purpose of this study was to make an Arduino Uno-based doppler effect practicum tool with a Max4466 sensor, to find out the results of testing an Arduino Uno-based doppler effect practicum tool with a Max446 sound sensor. The research methodology used is linear regression of the instrument calibration experiment. The data of this research is data from the experimental results of practicum tools made with the calibration tool. This study states that the Max4466 Sound Sensor reads the frequency of sound then the data is processed and sent by Arduino Uno via commands on the Arduino IDE and the Data Streamer menu to Microsoft Excel. After that, the tool calibration process is carried out by comparing the frequency value between what is read on the sensor and the calibrator (digital multi-meter). This practicum tool innovation could directs teachers and students. The benefit of this research is to provide learning media that supports the teaching and learning process and improves students' skills. This research suggestion is for future researchers to look for other calibrators that can record data automatically to facilitate instrument calibration and conduct further research on the effect of air (environment) on a sound.